Nucleophilic conjugate trifluoromethylation of chromones and activated alkenes under the action of Ruppert’s reagent - V. Ya. Sosnovskikh; G.-V. Roshentaler (Chimica Techno Acta)
This review summarizes data on the reactions of chromones and activated alkenes with trimethyl(trifluoromethyl)silane (Ruppert’s reagent), which occures as a nucleophilic 1,4-trifluoromethylation with high regioselectivity and good yields. The most important chemical properties of the formed products are also considered.